APPLICATION OF GEOELECTRIC METHOD FOR AQUIFER IDENTIFICATION IN THE FOOT OF GAMALAMA VOLCANO ON SMALL VOLCANIC TERNATE ISLAND - Tanuhardjanto, Richard
A Ternate island is located on the west side of Halmahera island which passed by the zone of cincin api (Ring of Fire) so there is a volcano in it (Gamalama Volcano). The water availability in this island depends on the amount of groundwater recharge obtained through data processing which those datas is available on BMKG online site. In order to be able to map the distribution of groundwater in the aquifer, the 2D geoelectric modelling was carried out using Res2DInv and ResIPy applications with the validation of interpretation is using DHL and Salinity data and the geological map and the aquifer system map data. The supporting softwares used in this research are Surfer, ArcGIS, and Microsoft Excel. The result of geoelectric data modelling on the Jikomalamo line gives a resistivity values between 104.5 – 14744 ?m, while modelling on the Takome line gives resistivity values start from 99.2 – 1019.8 ?m, for the Tabam line geoelectric modelling has resistivity values ranging from 2.8 – 203.5 ?m, the geoelectric modelling of the Akehuda line gives resistivity values from 5 – 3382.8 ?m, the modelling on the PDAM line results resistivity values between 1.5 – 67.3 ?m, the modelling on the SKEP line shows resistivity values ranging from 58 – 896 ?m, the geoelectric modelling of the Kayu Merah line is in the range of resistivity values 14.1 – 411.8 ?m, the modelling on the Kalumata line gives resistivity values between 1.9 – 35.2 ?m, the geoelectric modelling of of the Fitu line shows resistivity values in the range of 16.2 – 43 ?m, and modelling on the Sasa line gives resistivity values start from 14.5 – 141.9 ?m. The groundwater resistivity values on all areas where geoelectric profiling applied are generally below 200 ?m while the seawater (brackish) resistivity values detected on aquifer occur in the PDAM line and Sasa line only are between values 0 up to 30 ?m. The average amount of groundwater recharge in a Ternate island at 2014 – 2021 peiod interval is 12 millions m3, so that approximately the amount of groundwater which enter and leave the aquifer must still have a equal volume to that value.